THE VALIDITY AND PRACTICALITY OF THE DEVELOPMENT OF LEARNING VIDEOS TO IMPROVE STUDENTS' SPEAKING ABILITY IN THE ELEVENTH GRADE - Anggun Mahesti; Hermansyah; Aswadi Jaya (Esteem Journal of English Education Study Programme, 2025)
English speaking is an important but often challenging skill for Indonesian students. This study aims to develop a learning video as an innovative solution to improve the students’ speaking ability of the eleventh, focusing on the validity and practicality of the media in the context of English language learning. The development of this learning video uses the ADDIE development model which consists of five stages namely Analysis, Design, Development, Implementation, and Evaluation. The validity of the learning video was assessed by material experts, media experts, and linguists based on certain aspects. The practicality of the learning video was assessed through student response questionnaires after using the video in learning. The results showed that the learning video developed was valid and practical to be used in improving the students’ speaking ability of the eleventh grade. Which in the study obtained an average percentage result with an assessment percentage from the validator of 97.6%, then the assessment of student responses obtained an average percentage of 86%. The implication of this research is the provision of alternative learning resources in the form of interesting and effective learning videos in supporting the teaching and learning process of English, especially to improve speaking ability.